Climate Change observations into Hydropower in Mozambique. (October 2017) - Uamusse, Miguel M.; Aljaradin, Mohammad; Nilsson, Erik; Persson, Kenneth M.
Abstract: Hydropower is a renewable energy that expected to be affected by persistent climate change in Mozambique. Variability of climate e.g. temperature and precipitation will contributors to future shortage of energy from renewable energy production especially for hydropower and biomass. This research reviews the impacts of climate change on the productions of hydropower in Mozambique. Furthermore, a statistical methods using regressions analysis was used to evaluate the future climate scenario. The result showed that the average temperature in first 10 years was 25.4°C and last 10 years was 26.3°C; this means that the gradient of temperature was 0.88°C. The temperature was increasing significant especial the between October-March in rainy season and coincident is summer season. Also the result showed that climate change will cause increased variability of precipitation and create drought which is pre-conditions problems for decreasing hydroelectric generation in Mozambique. With frequency drought, flood combining with trend of precipitations, Mozambique is one of the most vulnerable countries of climate change. It was concluded that Mozambique hydropower productions will have to face challenging future.